2012
DOI: 10.1093/infdis/jir872
|View full text |Cite
|
Sign up to set email alerts
|

Early Age at Time of Primary Epstein–Barr Virus Infection Results in Poorly Controlled Viral Infection in Infants From Western Kenya: Clues to the Etiology of Endemic Burkitt Lymphoma

Abstract: Children from a region at high risk for eBL were infected very early in life with EBV, resulting in higher viral loads throughout infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
205
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(218 citation statements)
references
References 29 publications
12
205
1
Order By: Relevance
“…Surprisingly, it remained about the same. Recent evidence suggests that infection with EBV at an early age increases the risk of developing EBV-related cancer (Piriou et al, 2012). Despite the burden of EBV-associated cancers, vaccine development is still in progress (Balfour, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, it remained about the same. Recent evidence suggests that infection with EBV at an early age increases the risk of developing EBV-related cancer (Piriou et al, 2012). Despite the burden of EBV-associated cancers, vaccine development is still in progress (Balfour, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations of EBV infections vary according to age, ranging from silent infections in infants to infectious mononucleosis in adolescents and adults. In addition, many serological and molecular studies have provided evidence that EBV is associated with various types of malignancies such as lymphoma, nasopharyngeal carcinoma (NPC), Hodgkin disease and gastric carcinoma (Cohen et al, 2008;Hjalgrim et al, 2000;Mitarnun et al, 2004;Piriou et al, 2012;Tiwawech et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Both infection with Epstein-Barr virus (EBV) and repeated episodes of Plasmodium falciparum malaria are known risk factors for eBL (2), but the mechanism(s) by which these two agents interact to promote the emergence of malignant B cell clones has not been elucidated. Recently, we found that infants from a region of malaria endemicity of western Kenya were infected with EBV by 6 months of age (3). Living in regions of malaria endemicity was a predictor of this early age of primary infection.…”
mentioning
confidence: 90%
“…Clinically, elevated levels of anti-VCA and anti-EBNA1 immunoglobulin G (IgG) antibodies have been used as evidence of past infection (9), while the presence of IgG antibodies to the EBV early antigens (EAd and Zta) generally reflects recent or reactivated infections (10,11). Although EBV-specific antibody patterns reflect the dynamics of EBV activity in adults, few studies have addressed this issue in infants and children (3,(12)(13)(14)(15) or in newborns (16,17). More importantly, no comparison to maternal antibody levels has been made and there has been no analysis of how maternal malaria infections impact transplacental transfer of EBV-specific antibodies.…”
mentioning
confidence: 99%
“…Burkitt lymphoma is more common among infants who have primary EBV infection at very early ages and the accompanying high EBV viremia [8] . Many studies have shown that EBV seroprevalence increases with age [7,[9][10][11] .…”
Section: Resultsmentioning
confidence: 99%